2010
DOI: 10.1080/22201173.2010.10872707
|View full text |Cite
|
Sign up to set email alerts
|

Rabies vaccine and neuraxial anaesthesia

Abstract: This case report of neuraxial anaesthesia for emergency orthopaedic surgery serves to highlight the dilemma faced by anaesthetists when surgical intervention becomes necessary in a patient on anti-rabies vaccine. The two issues of importance are the possible reduction in the ef cacy of vaccination by an immunosuppressive effect of anaesthesia and surgery, and the possible need to avoid local anaesthetics for the provision of postoperative analgesia to assist in the early detection of any neurological de cit.Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The key issues of importance are the possible reduction in the efficacy of the vaccine and the possible need to avoid local anaesthetic for post-operative analgesia to assist in the early detection of any neurological deficits. 5 Apart from a number of reasons contributing to post-exposure prophylaxis failure, ketamine anaesthesia has been mentioned as an additional risk factor for treatment failure. 5 The main concern in this patient was the probability of reduction in the efficacy of the vaccine due to immunosuppressive effect of anaesthesia and surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The key issues of importance are the possible reduction in the efficacy of the vaccine and the possible need to avoid local anaesthetic for post-operative analgesia to assist in the early detection of any neurological deficits. 5 Apart from a number of reasons contributing to post-exposure prophylaxis failure, ketamine anaesthesia has been mentioned as an additional risk factor for treatment failure. 5 The main concern in this patient was the probability of reduction in the efficacy of the vaccine due to immunosuppressive effect of anaesthesia and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5 Apart from a number of reasons contributing to post-exposure prophylaxis failure, ketamine anaesthesia has been mentioned as an additional risk factor for treatment failure. 5 The main concern in this patient was the probability of reduction in the efficacy of the vaccine due to immunosuppressive effect of anaesthesia and surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Nasogastric tube is essential for gastric decompression and remained on suction during induction and intubation to minimize the amount of gastric contents in the oropharynx. 2,6,7 Neonates coming for emergency surgery pose risk for anesthesia. Thorough understanding of physiological and pharmacological changes in neonates is important.…”
Section: Discussionmentioning
confidence: 99%
“…However, neuraxial anaesthesia may have medicolegal implications. V. Rewari et al .,[ 5 ] reported a case of intertrochanteric fracture femur done under neuraxial anaesthesia in a patient who was receiving ARV. The authors concluded that use of regional anaesthesia in patients receiving ARV needs further evaluation.…”
mentioning
confidence: 99%